Diversification of histone H2A variants during plant evolution. (July 2015) - Kawashima, Tomokazu; Lorković, Zdravko J.; Nishihama, Ryuichi; Ishizaki, Kimitsune; Axelsson, Elin; Yelagandula, Ramesh; Kohchi, Takayuki; Berger, Frederic
Highlights Flowering plants have evolved a large array of unusual histone variants. Three major features categorize H2A histones into distinct variant classes. Canonical H2A and H2A.X diverged already in green algae. Additional diversification of H2A.X took place gradually during land plant evolution. In addition to H2A.Z and H2A.X, the land plant ancestors evolved two variant classes H2A.M and H2A.W.